Selected Methods in the Process of Teaching a Chronically Ill Child at the Early School Stage - BABIARZ, MIROSŁAW; MAJDA, AGNIESZKA (Journal of Education, Technology and Computer Science, 2024)
The article discusses the definitions and models of chronic disease, and lists examples of diseases that are considered chronic diseases and fit into the classification of students with special educational needs. The role of chronically ill student in early school education and the goals that a teacher should set when working with a child are explained. The article contains considerations on selected methods of therapy for a child with a chronic disease.